Editorial - Jordan, Barry (New Cinemas: Journal of Contemporary Film, 2003)
"In a house there is the top floor and there is the cellar. The underground film-makers live in the same house as Hollywood, but they work in the cellar. It’s up to them if they like to live in the dark. The Hollywood filmmakers are more intelligent, because they have that sunny top floor." (Jean-Luc Godard) Godard’s house might not be an altogether convincing spatial metaphor for the current condition of world film-making, but recent reports are filled with gloomy predictions of the commercial difficulties of non-Hollywood Second and Third Cinemas. Is it the case that commercial film theatres are showing an ever-narrowing range of films, reinforcing the narrowness of audience tastes?
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9uY2luLjEuMy4xMzcvMA